Review: ischemic heart disease and the potential role of fenugreek (trigonella foenum graecum linn.) In cardioprotection - Hanafi, Noorul izzati; Saidan, Noor Hafizoh; Mohamed, Maizan; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Gan, Siew Hua; A.K. Pahirolzaman, Khomaizon; Rao, Pasupuleti Visweswara (UTM Press, 2022)
Ischemic heart disease, often known as coronary heart disease (CHD), is a term for heart disorders caused by narrowing heart arteries (coronary arteries) that provide blood to the heart's muscles. The body is prone to heart attacks when there is less oxygen supply (hypoxia) to the heart resulting a major cell death in the heart tissues. Cardiovascular disease (CVD) is the leading cause of death worldwide. Over the last few decades, the potential therapeutic effects of herbs and other types of complementary medicines for managing risk factors for CVD have gotten a lot of attention. Fenugreek (Trigonella foenum graecum Linn.) is a very important spice in most Asian dishes. In Malaysia, fenugreek, locally known as ‘halba’, is used in the preparation of popular dishes; ‘nasi dagang’ for breakfast, and ‘putu halba’ as snacks for hi-tea and sometimes applied in drinks. Although, to date, the effect of fenugreek against diabetes and heart diseases is well investigated, most studies do not focus on its the effects at molecular levels. This review gives an insight on the ischemic heart disease and the nutritional values of fenugreek as functional food in protecting the heart.